Histological and Transcriptomic Analysis of Adult Japanese Medaka Sampled Onboard the International Space Station - Murata, Yasuhiko; Yasuda, Takako; Watanabe-Asaka, Tomomi; Oda, Shoji; Mantoku, Akiko; Takeyama, Kazuhiro; Chatani, Masahiro; Kudo, Akira; Uchida, Satoko; Suzuki, Hiromi; Tanigaki, Fumiaki; Shirakawa, Masaki; et al. (PloS one, 2015)
To understand how humans adapt to the space environment, many experiments can be conducted on astronauts as they work aboard the Space Shuttle or the International Space Station (ISS). We also need animal experiments that can apply to human models and help prevent or solve the health issues we face in space travel. The Japanese medaka (Oryzias latipes) is a suitable model fish for studying space adaptation as evidenced by adults of the species having mated successfully in space during 15 days of flight during the second International Microgravity Laboratory mission in 1994. The eggs laid by the fish developed normally and hatched as juveniles in space. In 2012, another space experiment ("Medaka Osteoclast") was conducted. Six-week-old male and female Japanese medaka (Cab strain osteoblast transgenic fish) were maintained in the Aquatic Habitat system for two months in the ISS. Fish of the same strain and age were used as the ground controls. Six fish were fixed with paraformaldehyde or kept in RNA stabilization reagent (n = 4) and dissected for tissue sampling after being returned to the ground, so that several principal investigators working on the project could share samples. Histology indicated no significant changes except in the ovary. However, the RNA-seq analysis of 5345 genes from six tissues revealed highly tissue-specific space responsiveness after a two-month stay in the ISS. Similar responsiveness was observed among the brain and eye, ovary and testis, and the liver and intestine. Among these six tissues, the intestine showed the highest space response with 10 genes categorized as oxidation-reduction processes (gene ontogeny term GO:0055114), and the expression levels of choriogenin precursor genes were suppressed in the ovary. Eleven genes including klf9, klf13, odc1, hsp70 and hif3a were upregulated in more than four of the tissues examined, thus suggesting common immunoregulatory and stress responses during space adaptation.